Environmental and geographical characteristics affecting the productivity of citrus farms in Lattakia Governorate - محمود, رامي; محمود عليو; جرجس مخول (Latakia University Journal -Biological Sciences Series, 2022)
This research aims to determine environmental and geographical characteristics that affect Citrus farms productivity in latakia. Governate The research has been conducted using on-site form for the season (2020-2021) distributed to a random sample of farmers with a number of 380 farmer. The research depended on the descriptive and analytical method concentrating on Using a multiple linear regression model to express the function of the production of each citrus cultivar. This study concluded that frost, Aleyrodidae, and altitude are the main determinants of cultivating different citrus cultivars in the study sample while the other factors (Mal secco- phyllocnistis citrella- citrus scab- Mites- Aonidiella aurantii- salinity - lime - slope - moisture - distance from sea level) did not perform productivity differentiation at the level of one variety in the study sample which indicates that variation in the values ​​of these factors is not sufficient to create significant differences or variations in the productivity of one variety, and the effect of environmental and geographical factors on the productivity of citrus varieties in the study sample ranges between 21%-38% and It has a significant effect at the 1% level. These results do not represent the experiment conditions that allow focusing on specific factors and isolating the influence of other factors. As a result, the absence of the influence of some factors in the farm conditions appears in one way or another as if these factors are considered constant among the farms or that their variance was not sufficient to produce the effect assumed in theory.